Recall and decay of consent information among parents of infants participating in a randomized controlled clinical trial using an audio-visual tool in The Gambia - Robert B. Mboizi; Muhammed O. Afolabi; Michael Okoye; Beate Kampmann; Anna Roca; Olubukola T. Idoko (Taylor & Francis Group, 2017)
Communicating essential research information to low literacy research participants in Africa is highly challenging, since this population is vulnerable to poor comprehension of consent information. Several supportive materials have been developed to aid participant comprehension in these settings. Within the framework of a pneumococcal vaccine trial in The Gambia, we evaluated the recall and decay of consent information during the trial which used an audio-visual tool called 'Speaking Book', to foster comprehension among parents of participating infants. The Speaking Book was developed in the 2 most widely spoken local languages. Four-hundred and 9 parents of trial infants gave consent to participate in this nested study and were included in the baseline assessment of their knowledge about trial participation. An additional assessment was conducted approximately 90 d later, following completion of the clinical trial protocol. All parents received a Speaking Book at the start of the trial. Trial knowledge was already high at the baseline assessment with no differences related to socio-economic status or education. Knowledge of key trial information was retained at the completion of the study follow-up. The Speaking Book (SB) was well received by the study participants. We hypothesize that the SB may have contributed to the retention of information over the trial follow-up. Further studies evaluating the impact of this innovative tool are thus warranted.